Plant Biology and Biotechnology 2015
DOI: 10.1007/978-81-322-2286-6_9
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Applications of Mushrooms

Abstract: Mushrooms which are earliest known fl eshy fungi are widely distributed in tropical temperate regions alike. They are attractive in colour, design and shape and intimately associated with human civilization. They are ubiquitous saprophytes as well as symbiotic in nature. Though many are edible and have medicinal properties, some are deadly poisonous and are called toadstools. Taxonomically they represent ascomycotina and basidiomycotina. They can be active and produce variety of metabolites exhibiting wide-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Further, there were also anti-viral studies observed on the reverse transcriptase activity on the immunodeficiency virus (HIV-1) which showed inhibitory function. Usually, edible mushrooms possess between 19 to 39% of protein by dry weight while being a part of a complex network of fungal cells ( Reddy, 2016 ).…”
Section: Active Metabolite From Mushroommentioning
confidence: 99%
“…Further, there were also anti-viral studies observed on the reverse transcriptase activity on the immunodeficiency virus (HIV-1) which showed inhibitory function. Usually, edible mushrooms possess between 19 to 39% of protein by dry weight while being a part of a complex network of fungal cells ( Reddy, 2016 ).…”
Section: Active Metabolite From Mushroommentioning
confidence: 99%
“…They are the best‐known source of nutrition, medicine, tonic, including and are considered good substitutes for meat being highly rich in protein (35%; Thakur, 2020). They are low lipid, sugar, and calories, possessing superior nutritive value than eggs, meat and pulses (Reddy, 2015).…”
Section: Introductionmentioning
confidence: 99%